Social Investing Modeling for Sustainable Development of the Russian Arctic - Andrey Novoselov; Ivan Potravny; Irina Novoselova; Violetta Gassiy (Sustainability, 2022)
The method of the social investing of the Arctic subsoil users is considered in this article. As the portfolio of social investments is formed based on the interests of indigenous peoples, the authors used expert assessment and sociological research for social investing modeling. A two-stage procedure for forming a portfolio of such projects is proposed. An approach has also been developed for assessing and selecting investment projects for the Arctic sustainable development according to different criteria of optimality. The authors substantiate the need for a new approach to sustainable development of the Arctic, based not on compensation for the negative consequences of industrial development used in many countries, but on social investment. In this article the proposed approach is tested on the case of the Arctic indigenous community in Taimyr and the optimal social investing portfolio is justified.